Work-based Learning: Integrating Academia, Industry, and Community - Mann, Cody; Johnson, Bart; Ulseth, Ron; Ulseth, Katherine (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
This research paper presents a comprehensive analysis of a work-based learning model based on the principles of PBL and its positive synergistic effect on students, industries, and communities. The model is active in multiple communities in the United States. This paper will focus on the synergistic effect in a rural region of the upper Midwest. The model integrates academic instruction with hands-on industry experience, cultivating a collaborative environment that prepares future engineers to address complex challenges. The paper explores how the model’s partnerships with local and regional industries provide students with immersive, real-world learning experiences that enhance technical competencies, boost employability, and foster a mindset of lifelong learning. The paper also explores how industry partnerships drive innovation and generate social and economic benefits for the region, contributing to its resilience and growth. By supplying a skilled workforce to local industries, the model plays a critical role in community development, addressing both immediate industry needs and long-term sustainability. Additionally, the paper underscores the importance of community engagement, demonstrating how an integrated approach between academia, industry, and local stakeholders can yield significant advancements in engineering education and societal progress. The findings offer insights into the transformative potential of work-based learning models linking education, industry, and community engagement, advancing engineering education and broader societal development.